The role of actin cytoskeleton component Arp2/3 in inflammatory response - Xing, Jianxiao; Wang, Ying; Liang, Yanyang; Li, Jiao; Yao, Yuanjun; Li, Junqin; Zhang, Kaiming (Frontiers in Cell and Developmental Biology, 2025)
Actin regulatory protein plays an important role in immune-related diseases and affects cellular behavior by regulating the dynamic changes of the cytoskeleton. This regulation is crucial for maintaining the fine balance in the body’s biological processes, and can effectively prevent and control the occurrence and development of acute or chronic inflammation, thereby avoiding the appearance of various diseases. The Arp2/3 complex, an evolutionarily conserved molecular machinery, regulates actin cytoskeleton dynamics and nucleates branched actin networks. Upon activation, the Arp2/3 complex binds to the lateral face of pre-existing actin filaments and nucleates daughter filament assembly, generating branched actin networks through this Y-junction formation mechanism. However, the research on how actin is involved in regulating the inflammatory process has only gradually become clear recently. The article mainly summarizes the functions of the actin cytoskeleton, the role of the Arp2/3 complex, and its specific functions in the inflammatory response.